Mechanisms of Stroke after Intracranial Angioplasty and Stenting in the SAMMPRIS Trial - Derdeyn, Colin P (2013)
BACKGROUND: Enrollment in the Stenting and Aggressive Medical Management for the Prevention of stroke in Intracranial Stenosis (SAMMPRIS) trial was halted owing to higher than expected 30-day stroke rates in the stenting arm. Improvement in peri-procedural stroke rates from angioplasty and stenting for intracranial atherosclerotic disease (ICAD) requires an understanding of the mechanisms of these events. OBJECTIVE: To identify the types and mechanisms of peri-procedural stroke after angioplasty and stenting for ICAD. METHODS: Patients that suffered a hemorrhagic or ischemic stroke or a cerebral infarct with temporary signs (CITS) within 30 days of attempted angioplasty and stenting in SAMMPRIS were identified. Study records, including case report forms, procedure notes, and imaging were reviewed. Strokes were categorized as ischemic or hemorrhagic. Ischemic strokes were categorized as perforator territory, distal embolic, or delayed stent thrombosis. Hemorrhagic strokes were categorized as subarachnoid or intraparenchymal. Causes of hemorrhage (wire perforation, vessel rupture) were recorded. RESULTS: Three patients suffered an ischemic stroke after diagnostic angiography. Two were unrelated to the procedure. Twenty-one patients suffered an ischemic stroke (n= 19) or CITS (n=2) within 30 days of angioplasty and stenting. Most (n=15) were perforator territory and many of these occurred after angiographically successful angioplasty and stenting of the basilar artery (n = 8). Six patients suffered subarachnoid hemorrhage (three from wire perforation) and seven a delayed intraparenchymal hemorrhage. CONCLUSION: Efforts at reducing complications from angioplasty and stenting for ICAD must focus on reducing the risks of regional perforator infarction, delayed intraparenchymal hemorrhage, and wire perforation.